Design of Warehouse Management Application Tool for Controlling The Supply Chain - Anita Ratnasari; Edi Kartawijaya (International Conference on Engineering and Technology Development (ICETD), 2012)
Warehouse has a broad meaning and is more than just storage, but has more function than that such as receipt of goods,  placement of goods, arrangement of stock, the movement of goods, the release of goods, delivery of goods which are all required software to assist in the process of the above. Warehouse management System is a key element in the supply chain, where the main goal is to control all the process that occure in it such as shipping, receiving, storage, movement and retrieval. With Warehouse Management System we can control the process of moving and storage with better use of warehouse space to be optimize, improving the effectiveness of the process of acceptance and delivery as well as knowing the amount of stock with greater accuracy at any time.